Antithrombotic medication and endovascular interventions associated with short-term exposure to particulate air pollution: A nationwide case-crossover study. (November 2020) - Scheers, Hans; Nawrot, Tim S.; Nemery, Benoit; De Troeyer, Katrien; Callens, Michael; De Smet, Frank; Van Nieuwenhuyse, An; Casas, Lidia
Abstract: Short-term exposure to air pollution has pro-thrombotic effects and triggers thrombo-embolic events such as myocardial infarction or stroke in adults. This study evaluates the association between short-term variation in air pollution and treatments for acute thrombo-embolic events among the whole Belgian population. In a bidirectional time-stratified case-crossover design, we included 227, 861 events treated with endovascular intervention and 74, 942 with antithrombotic enzymes that were reimbursed by the Belgian Social Security between January 1st, 2009 and December 31st, 2013. We compared the concentrations of particulate matter (PM) air pollution (PM10 and PM2.5 ), as estimated at the municipality level on the day of the event (lag 0) and two days earlier (lag 1 and lag 2) with those of control days from the same month, matched by temperature and accounting for day of the week (weekend vs week days). We applied conditional logistic regression models to obtain odds ratios (OR) and their 95% CI for an increase of 10 μg/m 3 (PM10 ) or 5 μg/m 3 (PM2.5 ) in pollutant concentrations over three lag days (lag 0, 1 and 2). We observed significant associations of PM10 and PM2.5 with treatment of acute thrombo-embolic events at the three lags. The strongest associations were observed for air pollution concentrations on the day of the event (lag0). Increases of 10 μg/m 3 PM10 and 5 μg/m 3 PM2.5 on lag0 increased the odds of events treated with endovascular intervention by 2.7% (95%CI:2.3%–3.2%) and 1.3% (95%CI:1%–1.5%), respectively, and they increased the odds of events treated with antithrombotic enzymes by 1.9% (95%CI:1.1–2.7%) and 1.2% (95%CI:0.7%–1.6%), respectively. The associations were generally stronger during autumn months and among children. Our nationwide study confirms that acute exposure to outdoor air pollutants such as PM10 or PM2.5 increase the use of medication and interventions to treat thrombo-embolic events. Graphical abstract: Image 1 Highlights: Air pollution has pro-thrombotic effects and may trigger thrombo-embolic events. This case-crossover study includes 302, 803 treatments for thrombo-embolic events. Environmental pollutants are associated with treatments for thrombo-embolic events. This study suggests higher health care expenses on days with high air pollution levels.